Pengaruh Customer Experience dan Complaint Handling Terhadap Customer Satisfaction Pada Nasabah Yang Melakukan Transaksi di PT.Bank Sumut KCP Syariah HM Joni Medan - Nadya Andayani; Tuti Anggraini (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the effect of customer experience and complaint handling on customer satisfaction in customers who make transactions at PT. Bank Sumut KCP Syariah HM Joni Medan. The methodology used is a quantitative approach. The sample in this study were all customers who made transactions at Bank Sumut KCP Syariah HM Joni Medan of 100 people. The data in this study were obtained by distributing questionnaires in the form of Google forms and testing data analysis using SPSS 25. The results showed that simultaneously all independent variables had an effect on the dependent variable, Simultaneous Test variables X1 and X2 had a significant effect on Customer Satisfaction (Y) this can be proven by the value of 24,040 > 3.090 meaning that F count is greater than F table (F count > F table). So it can be concluded that the variables X1 and X2 simultaneously have a significant effect on the dependent variable Y. Meanwhile, partially the effect of each variable X1 and X2 on Y has an effect, meaning that X1 can be proven by the value of T table 6.869 > 1.98, namely the calculated F value is greater than the value F table so that it can be concluded that there is a partial effect. Whereas X2 has no effect, this is evidenced by its significance value of 0.152 > 0.05 or the calculated T value with T table -1443 < 1.98 which is larger T table than T calculated and its significance value is also greater than the predetermined value of 0.05 so it can be concluded X2 has no partial effect. The results of the determination test for the R-squared value show a result of 0.331 or 33%, so the conclusion is that customer satisfaction at PT. Bank Sumut KCP Syariah HM Joni Medan is 33% influenced by Customer Experience (X1) and Complaint Handling (X2) on Customer Satisfaction (Y) while the remaining 67% is influenced by other variables outside the model in this study.